Peningkatan Partisipasi Mahasiswa Melalui Penerapan Model Pembelajaran Jigsaw pada Mata Kuliah Pendidikan Kewarganegaraan - Nurlatifa; Mukhamad Murdiono; Suyato (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Several factors influence the low level of student participation. One of the causes of low student learning participation in citizenship education courses is the use of learning models during lectures. This research aims to increase student participation by applying the Jigsaw learning model in the Citizenship Education course. This research uses mixed methods, namely combining qualitative and quantitative research. Quantitative methods were used for questionnaire instruments to collect data on student participation levels after implementing the jigsaw learning model. In contrast, qualitative methods were used to analyze data using the Miles and Huberman model of qualitative data analysis, which consists of data reduction, data presentation, and concluding. The subjects in this research were management study program students studying citizenship. The research results show increased student participation in Citizenship Education courses after implementing the Jigsaw learning model, with an average achievement of 88%, which is included in the high criteria. The Jigsaw learning model is appropriate because it can increase student participation in Citizenship Education courses.